1903 S.D. Sess. Laws 168-69, ch. 144, §§ 1-3 - (:unkn) unknown (My University, 1903)
It shall be unlawful for any person under the age of fifteen years to carry, use or discharge any rifle, shot gun, revolver or other fire arms except with the consent and knowledge of their parents or guardians. § 2. It shall be unlawful for any parent or guardian, having the legal charge or control of any minor under the age of fifteen years, to allow or permit such minor to use or carry while loaded any of the arms mentioned in section one of this act within the platted portion or within the distance of one mile of the platted portion of any city, town or village. § 3. Any person or persons violating the provisions of this act shall be deemed guilty of a misdemeanor and upon conviction thereof shall be fined in a sum not exceeding Fifty Dollars.
Keywords: DISCHARGE; POSSESSION - MINORS